Increased oxidative stress, hyperphosphorylation of tau, and dystrophic microglia in the hippocampus of aged Tupaia belangeri. Issue 9 (25th February 2020) - Rodriguez‐Callejas, Juan D.; Fuchs, Eberhard; Perez‐Cruz, Claudia
Abstract: Aging is a major risk factor for the development of neurodegenerative diseases. Alzheimer's disease and other neurodegenerative diseases are characterized by abnormal and prominent protein aggregation in the brain, partially due to deficiency in protein clearance. It has been proposed that alterations in microglia phagocytosis and debris clearance hasten the onset of neurodegeneration. Dystrophic microglia are abundant in aged humans, and it has been associated with the onset of disease. Furthermore, alterations in microglia containing ferritin are associated with neurodegenerative conditions. To further understand the process of microglia dysfunction during the aging process, we used hippocampal sections from Tupaia belangeri (tree shrews). Adult (mean age 3.8 years), old (mean age 6 years), and aged (mean age 7.5 years) tree shrews were used for histochemical and immunostaining techniques to determine ferritin and Iba1 positive microglia, iron tissue content, tau hyperphosphorylation and oxidized‐RNA in dentate gyrus, subiculum, and CA1‐CA3 hippocampal regions. Our results indicated that aged tree shrews presented an increased number of activated microglia containing ferritin, but microglia labeled with Iba1 with a dystrophic phenotype was more abundant in aged individuals. With aging, oxidative damage to RNA (8OHG) increased significantly in all hippocampal regions, while tau hyperphosphorylation (AT100) was enhanced in DG, CA3, and SUB in aged animals. Phagocytic inclusions of 8OHG‐ and AT100‐damaged cells were observed in activated M2 microglia in old and aged animals. These data indicate that aged tree shrew may be a suitable model for translational research to study brain and microglia alterations during the aging process. Abstract : Aged tree shrews had an enhanced number of activated and dystrophic microglia, 8OHG, iron tissue content and AT100 in the hippocampus compared to younger animals. M2 microglia from old and aged tree shrews presented 8OHG‐ and AT100‐phagocytic inclusions.